2012
DOI: 10.1111/j.1600-0765.2012.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azithromycin, as an adjunct to nonsurgical periodontal treatment, on microbiological parameters and gingival crevicular fluid biomarkers in generalized aggressive periodontitis

Abstract: Adjunctive azithromycin therapy provides no additional benefit over nonsurgical periodontal treatment on clinical parameters, microbiological parameters and gingival crevicular fluid biochemical markers investigated in patients with generalized aggressive periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
95
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(106 citation statements)
references
References 56 publications
6
95
2
Order By: Relevance
“…Interestingly, MMP‐1, MMP‐8, MMP‐9, MMP‐12, and MMP‐13 have all been shown to be related to periodontal disease process, and they all showed a significant reduction over time after treatment of LAgP, as well as a positive correlation with each other 8,11,23 . Reductions of MMP‐8, MMP‐9, and MMP‐13 after periodontal treatment have also been reported previously 21 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, MMP‐1, MMP‐8, MMP‐9, MMP‐12, and MMP‐13 have all been shown to be related to periodontal disease process, and they all showed a significant reduction over time after treatment of LAgP, as well as a positive correlation with each other 8,11,23 . Reductions of MMP‐8, MMP‐9, and MMP‐13 after periodontal treatment have also been reported previously 21 …”
Section: Discussionsupporting
confidence: 74%
“…To date, very few studies reported effects of different periodontal treatment approaches for AgP on MMP levels. Recently, Emingil et al 21 demonstrated that over a 6‐month period after periodontal treatment MMP‐8 levels in the GCF significantly decreased, along with clinical and microbiologic improvements. However, the authors used either SRP or adjunctive azithromycin therapy, and the population in the study consisted of generalized AgP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Emingil et al treated 32 GAP patients with nonsurgical therapy with or without AZT and found that all clinical parameters improved, and the microbiological parameters and gingival crevicular fluid matrix metalloproteinase-8 levels decreased significantly in both groups. [33] They found that AZT exerts no beneficial effect compared to nonsurgical periodontal therapy in GAP patients. In 2010, Hirsch reported three cases of chronic or aggressive periodontitis who received AZT adjunctive to nonsurgical treatment; in all cases the periodontal inflammation resolved and pocket depth decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The present study there was significant improvement in PI, GI, PD and HbA1cin both the groups but there was significant improvement in group II when compared to group I. In a randomized double-blind placebocontrolled parallel-designed studies by Emingil et al 10 Gomi et al 11 , Oteo et al 12 , Smith et al 13 …”
Section: Discussionmentioning
confidence: 88%